2002
DOI: 10.1038/sj.leu.2402608
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cells prevent apoptosis of AML cells by up-regulation of anti-apoptotic proteins

Abstract: The aim of this study was to study interactions between stromal bone marrow microenvironment and leukemic cells. We tested the hypothesis that stromal cells prevent apoptosis of AML cells by up-regulating anti-apoptotic proteins in leukemic blasts. In HL-60 and NB-4 cells, serum deprivation-and ara-Cinduced apoptosis was diminished when cells were cocultured with murine MS-5 stromal cells (P Ͻ 0.02). This effect was reproduced with conditioned medium from MS-5 cells. Cocultivation with stromal cells induced Bc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
297
3
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(325 citation statements)
references
References 65 publications
23
297
3
2
Order By: Relevance
“…23 The previous study also showed that coculture with CXCL12-producing stromal cell diminished ara-C-induced apoptosis in leukemic cells by BCL-2 upregulation. 19 Therefore, under a similar mechanism, increased expression of CXCL12 might be associated with the chemoresistance of CD34 þ hematopoietic cells in MDS/ AML-MRC bone marrow. CXCL12-abundant reticular cells are known to be major producers of SCF in the bone marrow, 5 and we found that the MDS bone marrow expresses high levels of SCF.…”
Section: Discussionmentioning
confidence: 99%
“…23 The previous study also showed that coculture with CXCL12-producing stromal cell diminished ara-C-induced apoptosis in leukemic cells by BCL-2 upregulation. 19 Therefore, under a similar mechanism, increased expression of CXCL12 might be associated with the chemoresistance of CD34 þ hematopoietic cells in MDS/ AML-MRC bone marrow. CXCL12-abundant reticular cells are known to be major producers of SCF in the bone marrow, 5 and we found that the MDS bone marrow expresses high levels of SCF.…”
Section: Discussionmentioning
confidence: 99%
“…Our group and others have shown that culturing of AML cells with SDF-1α (also known as CXCL12) promotes their survival, whereas adding neutralizing CXCR4 antibodies, SDF-1α antibodies, or the CXCR4 inhibitor AMD3100 significantly decreases it. BMderived mesenchymal stromal cells can also protect AML cells from chemotherapeutic drug-induced apoptosis (6,7). Moreover, weekly administration of anti-human CXCR4 antibody to mice previously engrafted with human AML cells leads to a dramatic decrease of human AML cells in BM, blood, and spleen in a dose-and time-dependent manner (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…About 35% to 50% of AML patients display a normal karyotype, which can further be subdivided using predictive molecular markers, such as mutations in the fetal liver tyrosine kinase-3 (FLT3) gene and the mixed-lineage leukemia (MLL) gene. 6,7 Several studies indicated that adhesion to marrow stromal cells affects the survival and proliferation of AML cells 8,9 and protects AML cells from chemotherapy in vitro 10 and in vivo. 11 Adhesion molecules, particularly the very late antigen-4 (VLA-4) and VLA-5 integrins, are considered essential for AML cell adhesion to respective stromal ligands (fibronectin) 12 and for protection of AML cells from spontaneous or drug-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%